The gospel of John - Saville, Philip; Drabinsky, Garth, 1949-; Michaels, Joel B.; Chrisafis, Chris; Goldsmith, John.; Cusick, Henry Ian.; Plummer, Christopher; Kash, Daniel; Lintern, Richard; Baszak, Miroslaw; Arcand, Michel, 1949-; Danna, Jeff.; et al. ([Toronto, Ont.] : Visual Bible International, 2005)
This feature film on the life, death and resurrection of Jesus is adapted from The Good News Translation Bible.
DVD; Widescreen (1.85:1)-Enhanced for 16x9 televisions; Dolby digital 5.1 Surround sound.
English, with subtitles in French and Spanish; Closed-captioned.
Henry Ian Cusick, Christopher Plummer, Daniel Kash, Richard Lintern.
Director of photography, Miroslaw Baszak ; editor, Michel Arcand ; music, Jeff Danna.
Originally released as a motion picture in 2003.
2-disc DVD includes new 2-hour version plus original 3-hour theatrical version.
Keywords: Jesus Christ -- Drama; Bible. -- Drama; Feature films; Religious films; Video recordings for hard of hearing people